2021
DOI: 10.1039/d0bm01735c
|View full text |Cite
|
Sign up to set email alerts
|

‘Golden’ exosomes as delivery vehicles to target tumors and overcome intratumoral barriers: in vivo tracking in a model for head and neck cancer

Abstract: Exosomes are promising vectors for anti-tumor therapy. In this research, both in-vivo CT tracking and ex-vivo measurements revealed better tumor targeting, accumulation and penetration of MSC-derived exosomes as compared to A431-derived exosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…The results clearly showed that the distribution of MSC-EXOs in the brain was closely related to inflammation [59]. Betzer et al [60] and Cohen et al [56] also used similar methods to evaluate the biodistribution of MSC-EXOs in the body. By studying the tracing of MSC-EXOs in the body, we can better research biodistribution, pharmacodynamics, targeting, etc.…”
Section: Evaluation Of Targeting Efficacymentioning
confidence: 98%
See 1 more Smart Citation
“…The results clearly showed that the distribution of MSC-EXOs in the brain was closely related to inflammation [59]. Betzer et al [60] and Cohen et al [56] also used similar methods to evaluate the biodistribution of MSC-EXOs in the body. By studying the tracing of MSC-EXOs in the body, we can better research biodistribution, pharmacodynamics, targeting, etc.…”
Section: Evaluation Of Targeting Efficacymentioning
confidence: 98%
“…Although researchers have conducted many experiments on MSC-EXOs, there is a lack of research on tracking and biodistribution in vivo [55]. At present, the primary methods for labeling MSC-EXOs in organisms are as follows: One is to wrap metal nanoparticles in exosomes, perform high-sensitivity magnetic resonance or CT analysis [52,56], use radioactive tracers and nuclear imaging for tracking [57], and stained with fluorescent dyes [58]. Perets et al developed a new visualization method that loaded glucose-coated GNPs (gold nanoparticles) into MSC-EXOs and used classical X-ray computed tomography (CT) to perform imaging to evaluate the biodistribution of MSC-EXOs in different pathological types of brain.…”
Section: Evaluation Of Targeting Efficacymentioning
confidence: 99%
“…The exosomes were discovered to be capable of targeting and accumulating at the tumor site for CT imaging. Therefore, GNPs combined with exosomes have great potential in clinical applications ( 111 ).…”
Section: Gold Nanoparticles Combined With Biomoleculesmentioning
confidence: 99%
“…Given their limited bioavailability, however, synthetic exosome-mimics have been used in their place to mediate endogenous and exogenous delivery for cancer treatment [ 12 ]. In particular, Cohen et al evaluated the parameters of exosomes derived from mesenchymal stem cells (MSC-exo) and A431 squamous cell carcinoma cells (A431-exo) as drug vectors and found MSC-exo to exhibit significantly greater tumor penetration and distribution in A431 tumor-bearing mice [ 38 ]. These results underscore that careful consideration should be given to an exosome’s type when applying it to drug delivery due to its unique properties and inherent targeting capabilities.…”
Section: Role Of Exosomes In the Diagnosis And Treatment Of Hnsccmentioning
confidence: 99%